PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SDN 3 PAHANDUT SEMESTER GENAP TAHUN PELAJARAN 2024/2025 - Irma Tri Rahayu; Joni Bungai; Melinda Prawati (Sangkalemo : The Elementary School Teacher Education Journal, 2025)
This research is motivated by the low learning outcomes of students in Pancasila Education subjects. This is evidenced by the fact that student learning outcomes have not met the Minimum Completeness Criteria (KKM) applied by the school with a score of 70. Out of 22 students, 5 students met the KKM and 17 students did not meet the KKM. This type of research is Classroom Action Research (CAR) using the Kemmis and Mc Taggart Model with four steps: 1) Planning, 2) Action, 3) Observation, and 4) Reflection. The subjects of this study were 22 fifth-grade students at SDN 3 Pahandut. The data collection techniques used were Tests (Initial Test and Final Test) and Observations, which were analyzed using qualitative and quantitative data. The results of this study indicate that application of the Teams Games Tournament (TGT) Learning Model can enhance student activity and learning outcomes. This evident from the observation results of student learning activities at the end of cycle I and cycle II. Additionally, student learning outcomes in each cycle showed an increase from the pre-test, which obtained a completeness percentage of 27.2% with average score of 55. After implementing actions in cycle I, student learning outcomes with a percentage of 63.6%. However, further improvements were necessary as it was not yet optimal, and subsequent actions in cycle II resulted in an average score of 81.8 with a completeness percentage reaching 86.4%. Thus, the completeness of student learning outcomes from the pre-test to cycle II experienced a 59.2% increase.